2006
DOI: 10.1016/j.jpeds.2006.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Cortical recruitment patterns in children born prematurely compared with control subjects during a passive listening functional magnetic resonance imaging task

Abstract: Objectives-To use functional magnetic resonance imaging (fMRI) to test the hypothesis that subjects who were born prematurely develop alternative systems for processing language.Study design-Subjects who were born prematurely (n = 14; 600-1250 g birthweight) without neonatal brain injury and 10 matched term control subjects were examined with a fMRI passive listening task of language, the Clinical Evaluation of Language Fundamentals (CELF) and portions of the Comprehensive Test of Phonological Processing (CTOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
49
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 43 publications
6
49
2
Order By: Relevance
“…The present study indicates the existence of neuronal markers of selective cognitive impairments at the age of 11 in EPT/ELBW children. The results fit nicely with the few previous fMRI studies of preterm children/adolescents (born <33 wk) looking at response inhibition (22), language (13,16,17,23), visual and auditory tasks (14,24), and verbal fluency (25), which also show reduced activation in preterm as compared with term-born children.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The present study indicates the existence of neuronal markers of selective cognitive impairments at the age of 11 in EPT/ELBW children. The results fit nicely with the few previous fMRI studies of preterm children/adolescents (born <33 wk) looking at response inhibition (22), language (13,16,17,23), visual and auditory tasks (14,24), and verbal fluency (25), which also show reduced activation in preterm as compared with term-born children.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have reported increased activation in areas unique to preterm children as compared with controls, and a suggested interpretation has been that they have developed alternative networks (16,17,22). We did not find evidence of increased activation in alternative networks in our preterm group.…”
Section: Fmri In Preterm Childrencontrasting
confidence: 76%
See 2 more Smart Citations
“…It is possible that VPT/VLBW children compensate for reduced regional cerebral volume [34] by recruiting supplementary brain regions to achieve the same level of performance as controls. Accordingly, VPT/VLBW children at 12 years of age were observed to activate different functional networks during a language processing task than controls, despite similar task performance [30]. Furthermore, catch-up might depend on environmental factors.…”
Section: Discussionmentioning
confidence: 91%